Practices and their Challenges in an English Teaching Project of a Brazilian State University during the Pandemic - Specht, André Luís (Educational Challenges, 2022)
The aim of this manuscript is to present, analyze and discuss the practices developed in a Teacher Education project called Residência Pedagógica (Pedagogical Residency) - a project that the Brazilian government offers to Brazilian universities - and their challenges during the pandemic. More specifically, it intends to focus on the practical phase of the first module of the project, which was when the project-participants observed classes in the school, designed lesson plans for the groups of whose classes they observed and implemented the lessons for these groups. Methodology. Qualitative research method was adopted in this study. The reports, lesson plans and video lessons of the project’s participants were used as data in order to analyze their practices under the light of theoretical discussion held during the project. A reflexive diary kept by me was also used as data. Moreover, the participants’ practices were contrasted with situations that occurred in the pandemic context. Results. The project practical phases did not occur as foreseen; however, the participants were able to reflect upon their practices based on the theoretical discussion carried out previously in the project. They recognized the language learning and teaching perspectives in the lessons they observed and, in the lesson, plans they designed and implemented. The pandemic had a great interference in the project, which had to be adapted, so that the first module could be concluded. Conclusions. In spite of the pandemic, we managed to reach the project’s main objective, which was to provide space for college students, who shall graduate as English teachers, to have contact with the school environment.